Autophagy in Pancreatic Acinar Cells in Caerulein-treated Mice: Immunolocalization of Related Proteins and Their Potential as Markers of Pancreatitis. (February 2014) - Zhang, Leshuai; Zhang, Jun; Shea, Katherine; Xu, Lin; Tobin, Grainne; Knapton, Alan; Sharron, Stewart; Rouse, Rodney
Drug-induced pancreatitis (DIP) is an underdiagnosed condition that lacks sensitive and specific biomarkers. To better understand the mechanisms of DIP and to identify potential tissue biomarkers, we studied experimental pancreatitis induced in male C57BL/6 mice by intraperitoneal injection of caerulein (10 or 50 μg/kg) at 1-hr intervals for a total of 7 injections. Pancreata from caerulein-treated mice exhibited consistent acinar cell autophagy and apoptosis with infrequent necrosis. Kinetic assays for serum amylase and lipase also showed a dose-dependent increase. Terminal deoxynucleotidyl transferase–mediated biotin-dNTP nick labeling (TUNEL) detected dose-dependent acinar cell apoptosis. By light microscopy, autophagy was characterized by the formation of autophagosomes and autolysosomes (ALs) within the cytoplasm of acinar cells. Immunohistochemical studies with specific antibodies for proteins related to autophagy and pancreatic stress were conducted to evaluate these proteins as potential biomarkers of pancreatitis. Western blots were used to confirm immunohistochemical results using pancreatic lysates from control and treated animals. Autophagy was identified as a contributing process in caerulein-induced pancreatitis and proteins previously associated with autophagy were upregulated following caerulein treatment. Autophagosomes and ALs were found to be a common pathway, in which cathepsins, lysosome-associated membrane protein 2, vacuole membrane protein 1, microtubule-associated protein 1 light chain 3 (LC3), autophagy-related protein 9, Beclin1, and pancreatitis-associated proteins were simultaneously involved in response to caerulein stimulus. Regenerating islet-derived 3 gamma (Reg3γ), a pancreatic acute response protein, was dose-dependently induced in caerulein-treated mice and colocalized with the autophagosomal marker, LC3. This finding supports Reg3γ as a candidate biomarker for pancreatic injury.